INTEGRATION OF MARKETING AND LOGISTICS WITHIN MODERN BUSINESS PROCESSES - BORTNIK, Anton; MILCHEVA, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article presents a comprehensive study of the integration of marketing strategies and logistics processes within the modern business processes of trade enterprises. It is established that integrating these functions is a vital tool for improving business efficiency in the context of globalization, digitalization, and rapid market changes. The role of market globalization, digital technologies, and the use of innovative tools, such as CRM systems and Big Data, in enhancing interaction between marketing and logistics is analyzed. The key role of the omnichannel approach is highlighted, which enables the integration of online and offline channels, creating a seamless experience for consumers while enhancing communication and improving customer service efficiency. The article also examines the use of artificial intelligence (AI) and the Internet of Things (IoT) to ensure speed, flexibility, and accuracy in supply chain management, optimizing logistics processes in real-time. Furthermore, it emphasizes the importance of integrating environmental and social factors into business development strategies, particularly in light of sustainable development and ESG (Environmental, Social, Governance) principles that ensure the long-term competitiveness of enterprises. To achieve effective synergy between marketing and logistics, the article proposes the author’s CMLI approach (Customer-centered Marketing–Logistics Integration), which is based on the phased development of integrating marketing and logistics functions. This approach facilitates the transition from basic coordination to complete adaptability of the system, enabling it to rapidly respond to changes in market conditions, demand, and resource availability. An essential element is the integration of data and technologies into a unified digital ecosystem that enables rapid decision-making and optimization of business processes. The article emphasizes the need for enterprises to adapt to contemporary requirements by effectively utilizing the latest technologies and sustainable practices, thereby ensuring long-term success and growth in a dynamic global environment.